The Influence Of Teacher Support On The Psychological And Emotional Development Of Junior High School Students In Yunnan Province - Wenjing, Chen; V. Panicker, Chandra Mohan (Journal of Neonatal Surgery, 2025)
This article aims to explore the impact of teacher support on junior high school students' non-cognitive abilities-Psychological and Emotional Development. By collecting and analyzing relevant data, the study examines the effects of three types of teacher support-emotional support, academic support, and behavioral support-on the development of students' non-cognitive abilities -Psychological and Emotional Development. Non-cognitive abilities -Psychological and Emotional Development encompass multiple dimensions such as conscientiousness, openness, extraversion, agreeableness, and neuroticism, which have significant impacts on students' personal growth and future development. The research results indicate that emotional support, academic support, and behavioral support provided by teachers all have significant positive effects on junior high school students' non-cognitive abilities -Psychological and Emotional Development. Emotional support helps enhance students' emotional security and self-confidence, thereby promoting the development of their non-cognitive abilities -Psychological and Emotional Development; academic support, by providing learning resources and guidance, assists students in improving their learning abilities and problem-solving skills, thereby positively influencing their non-cognitive abilities -Psychological and Emotional Development; and behavioral support, by regulating student behavior and encouraging their active participation in activities, shapes students' good behavior habits and social skills. Furthermore, the variables individual, family, and school levels were controlled to ensure the reliability and accuracy of the results. The findings show that, even after controlling all these variables, the impact of teacher support on non-cognitive abilities -Psychological and Emotional Development remains significant. In summary, this study reveals the important role of teacher support in the development of junior high school students' non-cognitive abilities -Psychological and Emotional Development, providing valuable insights and suggestions for educators. Teachers should focus on providing comprehensive support, including emotional, academic, and behavioral support, to promote students' overall development